The first comprehensive chemical profiling of Vachellia gummifera (Willd.) Kyal. & Boatwr., a plant with medicinal value - Kisiriko, Musa; Noleto-Dias, Clarice; Bitchagno, Gabin T. M.; Naboulsi, Imane; Anastasiadi, Maria; Terry, Leon A.; Sobeh, Mansour; Beale, Michael H.; Ward, Jane L. (Wiley, 2024)
Vachellia gummifera (Willd.) Kyal. & Boatwr. is a medicinal plant endemic to Morocco that has no documented studies on its chemical composition. In this study, the chemical composition of the water/methanol (4 : 1) extracts of air-dried leaf and stem samples of Moroccan V. gummifera was determined using UHPLC-MS and NMR. In total, over 100 metabolites were identified in our study. Pinitol was the major compound in both the leaf and stem extracts, being significantly more abundant in the former. Asparagine and 3-hydroxyheteroendrin were the second most abundant compounds in the stem and leaf extracts, respectively, though both compounds were present in each tissue. The other compounds included flavonoids based on quercetin, and phenolic derivatives. Eucomic acid, only identified in the stems and was the major aromatic compound distinguishing the leaf and stem profiles. Quercetin 3-O-(6′′-O-malonyl)-β-D-glucopyranoside was identified as the major flavonoid in the leaves but was also present in the stems. Other malonylated derivatives that were all flavonol glycosides based on myricetin, kaempferol, and isorhamnetin in addition to quercetin were also identified. This is the first report of eucomic acid and malonylated compounds in Vachellia species. This report provides valuable insights into the chemotaxonomic significance of the Vachellia genus.